Новые виды клещей рода Protogamasellus (Parasitiformes, Gamasina) из термитников Туркмении - Щербак, Г.И.; Петрова, А.Д. (Вестник зоологии, 1987)
P. bisclerotiodulus sp. n.— females are similar to P. primitivus, differ in scleronodules structure, presence of v-shaped projections on the anterior margin of the anterior dorsal shield, uneven sculpture line at D5 level, incrassated dorsal chaetae, shorter S6. P. elon-gatus sp. n.— females are similar to P. brevisetosus and P. dispar, differ in longer D8, scleronodules structure, wide incisions on ventro-anal shield, from P. brevisetosus — in the ventro-anal shield shape. P. ascleronodulus sp. n.— similar to P. bifurcalis, differs in longer dorsal chaetae, topography of D8 and VI5 in male and female, ventro-anal shield and spermatodactylus in male and metapodial shields in female.